Potential and Opportunity of Co-Firing Power Plant in Indonesia Through Torrefaction of Empty Fruit Bunch (EFB) - A Review - Irawan, Anton (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2021)
Electricity was an important requirement for various activities. Currently, the level of electricity consumption in Indonesia was around 1000 kWh/capita/year and is expected to continue to increase towards developed countries with a minimum electricity consumption level of 3000 kWh/capita/year. Along with the increasing demand for electricity, many new power plants were being built in Indonesia using coal as fuel. Coal was a non-renewable fuel so the CO2 gas produced has an impact on global warming. Co-Firing was a technology for combining fuel of biomass and coal in order to reduce the use of coal. The difference in the quality of biomass and coal was an obstacle to getting a stable combustion performance so it is necessary to improve the quality of biomass. The torrefaction technology can be implemented to improve the quality of biomass in Indonesia so it can be used as fuel for a co-firing power plant. One of the most potential biomass was empty fruit bunch (EFB) from palm oil processing with a potential of around 48 million tons per year or equivalent to 30 GW. Every Oil palm mills plant that process 25 ton/hour of fresh oil palm fruit bunches can produce EFB around 5.25 ton/hour. With so many palm oil plants, torrefaction technology can be used to store EFB torrefied which can change the properties of biomass from hydrophilic to hydrophobic. The government's role to support the use of biomass, including EFB, is very much needed in increasing cooperation between palm oil mills and power plants.